The Implementation of the Roles and Functions of Public Relations in Government Organizations - Anggun Nadia Fatimah; Safiat Amaylia Putri; Deby Puspitaningrum (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
This This study investigates the roles, organizational positioning, and media utilization of government public relations (PR) divisions in six Indonesian institutions within the context of digital public communication. Employing a qualitative design with in-depth interviews and thematic analysis, the study reveals that PR practitioners primarily perform communication facilitator and communication technician roles, focusing on information dissemination, media liaison, and operational communication tasks. The adoption of social media platforms such as Instagram, X, and YouTube has created opportunities for two-way interaction between government and citizens. However, findings indicate that such interactions remain largely transactional and rarely influence decision-making or policy formulation processes. Conceptually, this study enriches the literature on PR roles and functions, strategic communication, and public sector communication in the digital era. Practically, it recommends institutional reforms, professional capacity-building, and the integration of digital feedback into public communication planning to foster more participatory, transparent, and accountable government communication practices. Penelitian ini menganalisis peran, posisi organisasi, dan pemanfaatan media oleh humas pemerintah di enam institusi pemerintahan Indonesia dalam konteks digitalisasi komunikasi publik. Menggunakan pendekatan kualitatif dengan wawancara mendalam dan analisis tematik, studi ini mengungkap bahwa peran humas didominasi oleh communication facilitator dan communication technician, berfokus pada diseminasi informasi, hubungan media, serta aktivitas komunikasi teknis. Adopsi media sosial seperti Instagram, X, dan YouTube membuka ruang interaksi dua arah antara pemerintah dan masyarakat, namun temuan menunjukkan bahwa keterlibatan ini masih bersifat transaksional dan jarang memengaruhi proses pengambilan keputusan atau perumusan kebijakan. Secara konseptual, studi ini memperkaya literatur tentang peran dan fungsi humas, komunikasi strategis, dan komunikasi pemerintahan di era digital. Secara praktis, penelitian ini merekomendasikan reformasi kelembagaan, peningkatan kapasitas profesional, dan integrasi umpan balik digital ke dalam perencanaan komunikasi publik untuk mewujudkan komunikasi pemerintah yang lebih partisipatif, transparan, dan akuntabel.